Radionuclides: medicinal products or rather starting materials? - Oliver Neels; Marianne Patt; Clemens Decristoforo (SpringerOpen, 2019)
Abstract The EU directive 2001/83 describes the community code for medicinal products for human use including radiopharmaceuticals. In its current definition, also radionuclide precursors, such as fluorine-18, need to hold a marketing authorization before being placed on the market. The potential of novel radiopharmaceuticals for nuclear medicine is, although encouraged by European legislation and its respective guidance documents, therefore hampered by the regulatory framework. An update of EU directive 2001/83 would be beneficial for the development of novel radiopharmaceuticals and a safe advance in nuclear medicine.